Kampanye Lingkungan Sehat: Edukasi Sampah dan Pembuatan Tong Sampah dari Bahan Daur Ulang di RT 50 Kelurahan Bentungan Kota Bengkulu - Nutari, Puspita; Hastuti, Dea Silviana; Delpana, Adrian; Purnawan, Indah; Sipayung, Ronaldi; Rozzi, Yoli Andi; Nur’aini, Hesti; Fariadi, Herri (Jurnal Dehasen Mengabdi, 2025)
The healthy environment campaign activity aims to increase public awareness in maintaining cleanliness and managing waste independently. This campaign is carried out through waste sorting education, the use of eco-bricks as an alternative to plastic waste processing, making biopore holes for organic waste, and making trash bins from recycled materials. The location of the activity is in RT 50, Bentungan Village, Bengkulu City. The implementation method includes socialization, direct training, and practice with residents. The results of the activity show an increase in community participation in sorting and managing waste, as well as an increase in independent waste management facilities in the RT 50 environment.